2000
DOI: 10.1108/01437730010358161
|View full text |Cite
|
Sign up to set email alerts
|

Ethical preferences of transformational leaders: an empirical investigation

Abstract: This study looked at the relationship between the four factors of transformational leadership – charisma, inspirational leadership, intellectual stimulation, and individualized consideration – and the leader’s preference for unethical behavior. Five ethical scenarios – bribery, endangering the physical environment, lying, personal gain, and favoritism – were studied using a sample of 100 pairs of managers and subordinates from four multinational organizations in India. Relationships between the leader’s ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 29 publications
(26 reference statements)
2
78
0
2
Order By: Relevance
“…Burns (1978) argued that transformational leaders are likely to be guided by near universal values like equality of human rights and respect for individual dignity. Transformational leaders are also likely to resort to bribery and favoritism less frequently (Banerji and Krishnan, 2000), indicating the relatively greater importance they might give to values related to honesty and fairness. Therefore: Hypothesis 1.…”
Section: Rokeach's Value Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Burns (1978) argued that transformational leaders are likely to be guided by near universal values like equality of human rights and respect for individual dignity. Transformational leaders are also likely to resort to bribery and favoritism less frequently (Banerji and Krishnan, 2000), indicating the relatively greater importance they might give to values related to honesty and fairness. Therefore: Hypothesis 1.…”
Section: Rokeach's Value Surveymentioning
confidence: 99%
“…Ross and Offermann (1997) found that transformational leadership was positively related to self-confidence, feminine attributes, pragmatism, and nurturance, and negatively related to criticalness and aggression. Banerji and Krishnan (2000), in a study of transformational leaders' ethical preferences, found that that inspirational leadership was negatively related to the leader's the preference for bribery and favoritism, and intellectual stimulation was negatively related to preference for bribery. Transformational leaders rate themselves high on purpose-in-life, personal efficacy, interpersonal control, and social selfconfidence, while subordinates rate transformational leaders high on interpersonal control (Sosik and Megerian, 1999).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Bass argued that although transformational leadership and transactional leadership are conceptually distinct, they are likely to be displayed by the same individuals (Banjeri & Krishnan, 2000;Howell & Avolio, 1993). Transformational leadership and transactional leadership are seen to be a single continuum rather than mutually independent continua (Bass & Avolio, 1994;Northouse, 2004;Yammarino, 1993).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…The related contingency reward is the reward made available to followers for achieving goals. Although there are arguments supporting the effectiveness of transactional relations in achieving performance, an exclusive focus on the exchanges and transactions with followers has been criticized in the case of a) low expectations of followers and b) non-performing organizations (Banerji & Krishnan, 2000;Barbuto, 2005;Nahavandi, 2009). A particularly strong critique is that transactional leadership fails to inspire followers to reach for excellence, and focuses on short-term, immediate outcomes rather than on long-term commitment (Nahavandi, 2009), because the work environment of the follower does not provide the necessary motivation, direction and satisfaction (Den Hartog et al, 1997).…”
Section: Transactional Leadershipmentioning
confidence: 99%
“…Transformational leaders motivate and inspire followers to achieve extraordinary goals (Berson & Avolio, 2004), and are process-oriented (van Linden & Fertman, 1998). According to Banerji and Krishnan (2000), transformational leaders exploit the situation to launch and sustain the transformation process in organizations. To be able to do this, they must have the ability to articulate a compelling vision and to clarify any ambiguity that followers perceive, to ensure that everyone is following the new path.…”
Section: Transformational Leadershipmentioning
confidence: 99%